2003
DOI: 10.1046/j.1471-4159.2003.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the cyclin‐dependent kinase 5 activator, p35, by paclitaxel decreases β‐amyloid toxicity in cortical neurons

Abstract: One hallmark of Alzheimer's disease (AD) is the formation of neurofibrillary tangles, aggregated paired helical filaments composed of hyperphosphorylated tau. Amyloid-b (Ab) induces tau hyperphosphorylation, decreases microtubule (MT) stability and induces neuronal death. MT stabilizing agents have been proposed as potential therapeutics that may minimize Ab toxicity and here we report that paclitaxel (taxol) prevents cell death induced by Ab peptides, inhibits Abinduced activation of cyclin-dependent kinase 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 59 publications
(207 reference statements)
3
86
0
Order By: Relevance
“…Treatment with paclitaxel restores fast axonal transport in spinal axons, increases axonal MTs, and ameliorates motor impairments in tau transgenic mice that developed filamentous tau inclusions (mostly in the spinal cord) (Ishihara et al 1999(Ishihara et al , 2001Zhang et al 2005). Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003). Nanomolar concentrations of paclitaxel can protect neurons against various toxic insults and enhance survival by maintaining Ca 2+ homeostasis (Burke et al 1994;Furukawa and Mattson 1995;Furukawa et al 2003;Sponne et al 2003;Michaelis et al 2005) without evidence of toxicity (Trushina et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with paclitaxel restores fast axonal transport in spinal axons, increases axonal MTs, and ameliorates motor impairments in tau transgenic mice that developed filamentous tau inclusions (mostly in the spinal cord) (Ishihara et al 1999(Ishihara et al , 2001Zhang et al 2005). Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003). Nanomolar concentrations of paclitaxel can protect neurons against various toxic insults and enhance survival by maintaining Ca 2+ homeostasis (Burke et al 1994;Furukawa and Mattson 1995;Furukawa et al 2003;Sponne et al 2003;Michaelis et al 2005) without evidence of toxicity (Trushina et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Highly phosphorylated no longer stabilizes MTs, and intracellular aggregates of the protein are believed to cause disturbances in axonal transport of molecules and organelles in affected neurons (Lee, 1995). Recent studies have suggested that deposition of A␤ enhances phosphorylation in vitro in neuronal cell cultures (Busciglio et al, 1995;Ferreira et al, 1997;Grace et al, 2002;Li et al, 2003) and in vivo when A␤ is deposited in the brain (Sigurdsson et al, 1997;Geula et al, 1998).…”
mentioning
confidence: 99%
“…We previously reported that the MT-stabilizing agent paclitaxel (Taxol) significantly enhanced the survival of primary neurons in culture following exposure to A␤ [25][26][27][28][29][30][31][32][33][34][35] peptides, reduced activation of the apoptotic protease caspase 3, and blocked A␤-induced increases in abnormal phosphorylation (Michaelis et al, 1998;Li et al, 2003).…”
mentioning
confidence: 99%
“…It is reported that taxol prevents cell death induced by Abeta peptides, inhibits Abeta-induced activation of cdk5 and decreases tau hyperphosphorylation. 32 Taxol does not inhibit cdk5 directly but significantly blocks Abeta-induced calpain activation.…”
Section: Taxol Prion and Alzheimer's Diseasementioning
confidence: 95%